2021
DOI: 10.1021/acsami.1c01966
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Electron Interplay at the Fullerene/Sputtered TiOx Interface: A Barrier-Free Electron Extraction for Organic Solar Cells

Abstract: Organic photovoltaics (OPVs) technology now offers power conversion efficiency (PCE) of over 18% and is one of the main emerging photovoltaic technologies. In such devices, titanium dioxide (TiO x ) has been vastly used as an electron extraction layer, typically showing unwanted charge-extraction barriers and the need for light-soaking. In the present work, using advanced photoemission spectroscopies, we investigate the electronic interplay at the interface between low-temperature-sputtered TiO x and C70 acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The interface between fullerenes and titania has been deeply investigated. It was recently found that defect states in the band gap of titania are quenched by C 70 while an interfacial state appears, showing a barrier-free extraction of charges (Figure 3) for the next generation of organic solar cells [178]. However, in studies such as this one, fullerenes are added onto preformed titania.…”
Section: Fullerenesmentioning
confidence: 98%
“…The interface between fullerenes and titania has been deeply investigated. It was recently found that defect states in the band gap of titania are quenched by C 70 while an interfacial state appears, showing a barrier-free extraction of charges (Figure 3) for the next generation of organic solar cells [178]. However, in studies such as this one, fullerenes are added onto preformed titania.…”
Section: Fullerenesmentioning
confidence: 98%
“…Transport layer interface degradation is also well-known, in particular for many new non-fullerene based organic solar cell systems [236,237], for example due to photocatalytic decomposition of these molecules at metal oxide interfaces. This has made studies on transport layer interfaces very relevant for the OPV field [238]. For indoor PV, however, these effects are much less of an issue due to the lack of harsh and alternating weather conditions, and in particular, the different light spectrum and intensity at indoor conditions, i.e.…”
Section: Pv Generators For Iotmentioning
confidence: 99%
“…Energy levels of different CTMs, where the data are from: SnO 2 , 52 In 2 O 3 , 333 CdSe, 334 Nb 2 O 5 , 331 Fe 2 O 3 , 335 ZnO, 86 SnS 2 , 336 WO 3 , 331 Zn 2 SnO 4 , 337 TiO 2 , 282 TiS 2 , 338 ZnTiO 3 , 331 BaSnO 3 , 337 SrTiO 3 , 333 Bi 2 S 3 , 331 CdS, 331 GaN, 331 PCBM, 55 C 60 , 339 Bis‐C 60 , 339 C 70 , 340 ICBA, 339 PTB7‐Th, 341 Cu 2 O, 337 NiO x , 176 CuO, 337 CuSCN, 342 NiMgLiO, 342 V 2 O 5 , 342 CuI, 342 PCDTBT, 342 Poly(DTSTPF‐r‐BThTPD), 343 PBT, 342 PPP, 342 assy‐PBTBDT, 343 KTM3, 344 X‐QUPD, 342 X‐OTPD, 342 P6CT‐Na, 342 PPN, 342 PTAA, 345 PT, 342 Poly‐TPD, 176 P3HT, 343 Spiro‐OMeTAD, 158 PVB‐DAAF, 342 PEDOT:PSS, 78 and CPE‐K 342 …”
Section: Carrier Engineeringmentioning
confidence: 99%
“…Energy levels of different CTMs, where the data are from: SnO 2 , 52 In 2 O 3 , 333 CdSe, 334 333 Bi 2 S 3 , 331 CdS, 331 GaN, 331 PCBM, 55 C 60 , 339 Bis-C 60 , 339 C 70 , 340 ICBA, 339 PTB7-Th, 341 Cu 2 O, 337 NiO x , 176 CuO, 337 CuSCN, 342 NiMgLiO, 342 V 2 O 5 , 342 CuI, 342 PCDTBT, 342 Poly(DTSTPF-r-BThTPD), 343 PBT, 342 PPP, 342 assy-PBTBDT, 343 KTM3, 344 X-QUPD, 342 X-OTPD, 342 P6CT-Na, 342 PPN, 342 PTAA, 345 PT, 342 Poly-TPD, 176 P3HT, 343 Spiro-OMeTAD, 158 PVB-DAAF, 342 PEDOT:PSS, 78 and CPE-K. 342 during the preparation process, which improved the quality of cp-TiO 2 the film with highly uniform and pinhole free and effectively improved the efficiency and stability of (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.15 HPSC devices. Except for these metal ions, numerous function materials serve as additives to treat the TiO 2 films, such as Na 2 S, 374 TiCl 4 , 375,376 La 2 O 3 , 377 SbI 3 , 378 CsBr, 379 reduced graphene oxide (rGO), 380 C 60 , 381 and tetraethylammonium p-toluenesulfonate (TEATS).…”
Section: Electron Transport Materialsmentioning
confidence: 99%